Effects of Interferons and Viruses on Metabolism - Fritsch, Stephanie Deborah; Weichhart, Thomas (Frontiers in Immunology, 2016)
Interferons are potent pleiotropic cytokines that broadly alter cellular functions in response to viral and other infections. These alterations include changes in protein synthesis, proliferation, membrane composition, and the nutritional microenvironment. Recent evidence suggests that antiviral responses are supported by an interferon-induced rewiring of the cellular metabolism. In this review, we discuss the roles of type I and type II interferons in regulating the cellular metabolism and biosynthetic reactions. Furthermore, we give an overview of how viruses itself affect these metabolic activities to promote their replication. In addition, we focus on the lipid as well as amino acid metabolisms, through which interferons exert potent antiviral and immunomodulatory activities. Conversely, the expression of interferons is controlled by the nutrient sensor mammalian target of rapamycin (mTOR) or by direct reprogramming of lipid metabolic pathways. These findings establish a mutual relationship between interferon production and metabolic core processes.